ФОРМУВАННЯ ПІЗНАВАЛЬНОЇ МОТИВАЦІЇ СТАРШОКЛАСНИКІВ МЕТОДАМИ СТИМУЛЮВАННЯ НА УРОКАХ ІНОЗЕМНОЇ МОВИ (Педагогіка вищої та середньої школи, 2002)
The article deals with the principal ways of formation of senior pupils' cognitive motivation by means of methods of stimulation. The methods of stimulation, the use of which while teaching foreign languages positively influences the process of formation of cognitive motivation among senior pupils have been determined.